Limbal transplantation at a tertiary hospital in Brazil: a retrospective study - Moreira,Pedro Bertino (2015)
ABSTRACTPurpose:Epidemiological analysis of limbal transplantation surgeries performed in the Ophthalmologic Hospital of Sorocaba.Methods:Retrospective medical records review of 30 patients who underwent limbal stem cell transplants between January 2003 and March 2008. Cases involving conjunctival limbal autograft were classified as group I, and those involving conjunctival limbal allograft as group II.Results:Two patients were excluded due to incomplete data during postoperative follow-up. Of the total sample of 28 patients, 53.6% constituted group I, whereas 46.4% were included in group II. Males were predominant (67.9%), and right eyes were the most prevalent (67.9%). The mean age was 40.3 years. Unilateral cases accounted for 60.7%. The most frequent pathology causing limbal system failure was chemical burns (53%). The mean length of time from diagnosis to surgery was 11.18 years. The limbal graft and amniotic membrane were associated in 75% of all cases, and tarsorrhaphy in 57.1%. The average follow-up period was 24.84 months. The uncorrected visual acuity improved in 38% of the cases, was unchanged in 28.5%, and deteriorated in 33.3%. There was no persistent epithelial defect in 75% of the patients. The conjunctivalization rate was similar between the groups (53.3% and 58.3%, respectively). The transparency improved in only 38.4% of the cases, and 28.5% of the surgeries performed were successful. The most prevalent complication was persistent epithelial defect, which occurred in 25% of the patients, followed by corneal melting in 14.2%. Other complications observed included infectious ulcers, limbal graft necrosis or ischemia, perforation, and descemetocele.Conclusion:Chemical burns remain the main cause of limbal stem cell deficiency. In these cases, limbal transplantation is the standard procedure to restore the ocular surface even though the success rate is low.